(untitled) (International Journal of Food and Nutritional Sciences, 2022)
English Language in Business along with the discussion of ESP approach used for Business Purposes. This paper highlights the needs and uses of English language in business sectors. Business English (English for Business Purposes) is a new branch of ESP (English for Specific Purposes) which is a type of ELT (English Language Teaching). The students of commerce need a specific set of language skills for their success in their profession and place of Work. They are unable to use suitable words and expressions for their specific task due to lack of training and practice. This study focuses on the enhancement of business language skills for commerce students. The main purpose of this paper is to deal with the enhancement of a specific set of business terms and vocabularies of commerce students. Business English allied with the skills that most of the students need to improve their trades well.